2021
DOI: 10.17759/pse.2021260107
|View full text |Cite
|
Sign up to set email alerts
|

Developing Structural Components of Ecological Consciousness to Promote Civic Identity Formation

Abstract: The article deals with the development of structural components of environmental consciousness for the formation of an individual’s civic identity.The psychodiagnostic research was conducted using the data collected from the first- to fourth-year students.In total, 130 students from various fields of study participated in this study, including students in the Humanities, Natural Sciences, and Technology departments.The study was carried out using the techniques developed by the authors and the technique by S.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Therefore, the romantic tradition of literature has always played a genetic role in the reproduction of ecological thought. British and American romantic literature eulogizes the beauty of nature and writes that nature is an organic and unified whole, which stimulates people's ecological awareness of advocating, integrating, and respecting nature [ 5 ]. In the doubt of the rapid growth of the industrial society, under the obvious unreasonable utilization of resources and the pollution of the natural environment, the British and American romantic culture has grown rapidly and produced strong characteristics of the post industrial society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the romantic tradition of literature has always played a genetic role in the reproduction of ecological thought. British and American romantic literature eulogizes the beauty of nature and writes that nature is an organic and unified whole, which stimulates people's ecological awareness of advocating, integrating, and respecting nature [ 5 ]. In the doubt of the rapid growth of the industrial society, under the obvious unreasonable utilization of resources and the pollution of the natural environment, the British and American romantic culture has grown rapidly and produced strong characteristics of the post industrial society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experience is a fusion of emotion-centered sensibility and rationality, and strengthening the psychological experience of successful problem solving can effectively raise the level of individual self-esteem. The formation of virtue is the fusion of the subject and object of the individual's external “situation-event” and internal “experience-experience.” Therefore, the combination of helping individuals to solve problems and promoting psychological experiences can not only achieve the unification of perceptual awareness and rational discernment, but also balance the observational and experiential selves and effectively promote the formation of individual virtues [ 12 14 ].…”
Section: Related Workmentioning
confidence: 99%
“…e formation of virtue is the fusion of the subject and object of the individual's external "situation-event" and internal "experienceexperience." erefore, the combination of helping individuals to solve problems and promoting psychological experiences can not only achieve the unification of perceptual awareness and rational discernment, but also balance the observational and experiential selves and effectively promote the formation of individual virtues [12][13][14].…”
Section: Teaching Psychology and Civics In Higher Educationmentioning
confidence: 99%
“…Accepting environmental responsibility as a prerequisite for pro-ecological behavior, we set the goal of this study to identify the relationship of cognitive, value, emotional components of ecological consciousness and predisposition to environmental actions. Research in the field of environmental psychology suggested the following components of ecological consciousness as factors of environmental responsibility: ecological perceptions reflecting the role of the natural environment in human life [3,6,17]; environmental values [18,19]; concern about the impact of environmental threats [20,21]; the identity of the individual with the socio-natural environment [22,23].…”
Section: Introductionmentioning
confidence: 99%